The diagnostic value of ultrasound and mammography in detection of breast cancer in Albania - Ilirian Laçi; Leart Bërdica; Helidon Nina; Ilir Akshija; Alketa Spahiu; Ervin Toçi (Intelektual Pustaka Media Utama, 2023)
Early detection of breast cancer is essential for improving patient survival. However, non-invasive imaging test have different diagnostic value. This study aimed to assess the diagnostic accuracy of mammography and ultrasound to detect breast malignancy in Albania. The 234 patients suspected with breast lesions in Albania during 2018-2022 were subjected to both mammograph and ultrasound and then to core needle biopsy (CNB). The BI-RADS classification was used to evaluate breast lesions. The diagnostic value of ultrasound, mammography and their combination were assessed. Mean age of participants was 55.97 years (96.2% females). Ultrasound detected higher proportions of high-risk patients compared to mammography (79.1% vs. 52.6%, respectively) but the combination of the two increased this figure even further (88.9%). The sensitivity of mammography increased quickly with age, peaking to 93.2% among patients >60 years old, whereas ultrasound has better sensitivity among younger participants (<45 years and 45-60 years); overall, the combined tests had the highest sensitivity (95.1%), followed by ultrasound (87.4%) and mammography (59.3%). In conclusion, the sensitivity of mammography is best among older patients whereas ultrasound seems to be more accurate among younger patients. The combination of mammography and ultrasound seems to increase the diagnostic accuracy of breast tumors among Albanian patients.